Implementation of Prevention of Disturbance of Public Order in the Denpasar Police Area - Mahendra, Kadek Amen Putra; Karma, Ni Made Sukaryati; Sancaya, I Wayan Werasmana (Indonesian Journal of Law and Justice, 2025)
Studying the problems related to the effectiveness of preventing disturbances in order to maintain public order and security at the Denpasar City Police Resort is the main focus of this study. To overcome this problem, this study was conducted using an empirical method. The main source of legal information How to Collect Legal Documents Through Interviews and analysis of legal documents through analytical descriptions The results of the study found that the effectiveness of security and public disturbance prevention operations in the Denpasar Police Resort area was still not as good as expected. And there are still many cases of security disturbances and chaos. Although the patrol facilities and infrastructure are adequate, patrol activities are not the most appropriate activities. And there are still many cases of security and order disturbances in Denpasar City, such as motorcycle theft. The Dalmas Patrol Unit of the Denpasar City Samapta Police faces obstacles in preventing serious theft through patrols, such as the lack of facilities and infrastructure that can support or be useful for carrying out the patrol mission itself. Including other obstacles such as bad weather conditions Reducing visibility during patrols And there are several areas that cannot be accessed for patrol activities.